M12 Eligibility for lung cancer screening two years prior to lung cancer diagnosis – a multi-centre prospective study. (December 2018) - Gracie, K; Kennedy, MPT; Ellames, DAB; Hawramy, B; Ameri, A; Esterbrook, G; Blaxill, P; Smith, G; Smith, P; Naseer, R; Rodger, K; Robson, J; et al.
Abstract : Introduction: Low-dose CT screening for lung cancer is now available in North America according to criteria based on those used in the National Lung Screening Trial (NLST). Composite lung cancer risk prediction tools may increase the proportion of lung cancer patients eligible for screening. Our previous analysis 1 reported the proportion of lung cancer patients eligible for screening according to various criteria at the time of diagnosis. However, of more relevance is eligibility some time prior to diagnosis when early detection and treatment may reduce mortality. Based on an estimated sojourn time of 4 years, we assessed eligibility for screening 2 years prior to diagnosis. Methods: This is an extension of our previously published cohort 1 prospectively recruited from lung cancer fast-track clinics in West Yorkshire (Bradford, Calderdale and Huddersfield, Leeds, Mid-Yorkshire) from January–December 2016. Data was collected to allow assessment for eligibility according to the NLST criteria, USPSTF criteria (NLST extended to 80 years) and calculation (for ever-smokers) of lung cancer risk according to the Prostate Lung Colorectal and Ovarian score (PLCOM2012 ) and the Liverpool Lung Project score (LLP v2) 2 years prior to diagnosis. Results: 347 patients with lung cancer were identified of which 16 were excluded due to incomplete data collection. The percentage of lung cancer patients who would have been eligible by USPSTF and NLST criteria, together with percentages eligible at various thresholds of the two scores are shown in figure 1. The proportion of patients eligible 2 years prior to diagnosis were 35% for NLST, 46% for USPSTF, 59% for PLCO≥1.51% (55–75 year), and 34% for LLP ≥5% (55–75 year). 11% of patients would have been <55 years, 31%>75 years and 12%>80 years. 7% of those aged 55–80 years were never smokers. Discussion: The percentage of patients eligible for screening differs widely between potential screening criteria. If screening were available for a 55–75 year target age group, the majority of lung cancer patients would not have been eligible two years prior to their diagnosis using either NLST or USPSTF criteria and at almost all thresholds of the two risk scores. Reference: Gracie, et al. Thorax2016;71(Suppl 3):A76.